2009
DOI: 10.1097/ta.0b013e3181b57aa1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Clearance of the Cervical Spine in Blunt Trauma Patients Younger Than 3 Years: A Multi-Center Study of the American Association for the Surgery of Trauma

Abstract: CSI in patients younger than 3 years is uncommon. Four simple clinical predictors can be used in conjunction to the physical examination to substantially reduce the use of radiographic imaging in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
93
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(102 citation statements)
references
References 36 publications
7
93
0
2
Order By: Relevance
“…The eight factors identified in our parent study are supported by numerous smaller studies that identified high-risk MVC, as well as neurologic and neck physical examination findings, as being associated with CSIs in children. [2][3][4][5] Furthermore, the current study's findings reinforce the sensitivity of the original model in that applying age-stratified models did not improve the ability to detect CSI in the three separate age cohorts, particularly in children younger than 2 years old.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…The eight factors identified in our parent study are supported by numerous smaller studies that identified high-risk MVC, as well as neurologic and neck physical examination findings, as being associated with CSIs in children. [2][3][4][5] Furthermore, the current study's findings reinforce the sensitivity of the original model in that applying age-stratified models did not improve the ability to detect CSI in the three separate age cohorts, particularly in children younger than 2 years old.…”
Section: Discussionsupporting
confidence: 52%
“…The benefit of age-stratified models for CSI, particularly for the very young, is also supported by the findings of other investigators. 5,9 In a retrospective, multicenter trauma registry review of children younger than 3 years old, four factors demonstrated 100% sensitivity and 70% specificity for CSI: age 2 up to 3 years, Glasgow Coma Scale (GCS) score of <14, GCS eye opening score of 1, and MVC injury mechanism. A recent single-center retrospective review of young children with spine injury supports these findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These This article is part of the Topical Collection on Cervical Injuries and Treatment facts emphasize the need for an organized method for evaluation of the upper cervical spine in the pediatric population. While several studies have attempted to provide a "perfect" decision algorithm, the consensus seems to be that application of the National Emergency XRadiography Utilization Study (NEXUS) to children older than 9 years old is appropriate, while any concerning sign or symptom in a younger child should elicit a radiographic evaluation of the cervical spine [4,6].…”
Section: Pediatric Fractures Of the Atlasmentioning
confidence: 99%